(untitled) (Innovare: Revista de ciencia y tecnología, 2021)
Thermal map of Honduras built with images from the Landsat 8 satellite. It shows the possible geothermal potential sites in Honduras and their status. This observatory is the first platform of its kind available in the country, established to fill the gap in the access to energy data within the country by providing open access information related to energy industry. It uses information from multiple national and international data sources and combines 17 tabs in interactive dashboards showing statistics, measures, rates, weather data, satellite measures, wave energy potential and other data related to real time energy data. Available in t.ly/lq4W.